Generation Gap from Family Orientation Point of View: A Case on PT. Panggung Jaya Indah Textile - agustina, karina enny; Bawazir, Fatmah Cholid; Linawati (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
Family businesses account for 95 percent of all existing businesses in Indonesia, but only 12 percent survived to the third generation. The occurrence of various conflicts, differences, and problems in the family business gave rise to a well-known social stigma: the first generation builds, the second generation enjoys, and the third generation destroys. In this literature, the authors wish to examine the generation gap that exists at PT. Panggung Jaya Indah Textile/ PT Pajitex, a sarong manufacturer company with the brand "Sarung Mangga," from a family-oriented standpoint. In this study, the type of research used is descriptive qualitative research. Internal informants chosen are the owner of the company as the first generation and the owner’s daughter as the second generation. Meanwhile, Ciputra University’s main professor teaching a family business class on the Magister Management program has been chosen as an external informant of this literature. The findings of this research explain the generation gap problems between the first and second generations of PT. Pajitex and ways to overcome those obstacles.